Yahoo Web Search

  1. Sort by

  1. By multiplying the LHS by [1 - sin(2x)]/[1 - sin(2x)], we see that: LHS = [1 - 2sin^2(x)]/[1 + sin(2x...

    1 Answers · Science & Mathematics · 04/05/2011

  2. WHEN n = 1 LHS = 2 and RHS = 2 so correct n = 2 LHS = 2 + 8 = 10 RHS = 2...

    2 Answers · Science & Mathematics · 17/04/2008

  3. We have: a) LHS = cosθ + sinθtanθ = cosθ + sinθ(sinθ/cosθ) . . . . .tanθ = sinθ/cosθ = cos...tanθ. . . . . . . . . . . . . . . . . . . . . . . . . Tangent Identity = LHS I hope this helps!

    4 Answers · Science & Mathematics · 04/01/2010

  4. LHS= cos(3pi+x)= cos(2pi+pi+x)= cos(pi+x)= -cosx=..........(formula) RHS

    3 Answers · Science & Mathematics · 16/12/2009

  5. Method - 1 ........................................................................................... LHS = ( 1 + tan x ) / ( 1 + cot x ) ....... = ( 1 + tan x ) / [ 1 + ( 1 / tan x...

    1 Answers · Science & Mathematics · 12/01/2010

  6. LHS = a cos(pi/4) = 4root2 ---. a = 8

    1 Answers · Science & Mathematics · 15/12/2010

  7. Putting all on the LHS and re-arranging we have 5x^2-4x+5y^2+20y+19=0. Putting the 5 in...

    2 Answers · Science & Mathematics · 25/11/2010

  8. piece of cake. LHS = [ tan ( x - y ) + tany ] / [ 1 - tan ( x - y ) tan y ] LHS = tan ( x - y + y ) LHS = tan x LHS = RHS QED you do the other one.

    1 Answers · Science & Mathematics · 28/06/2013

  9. Taking the LHS and converting it to the RHS LHS = sin^2(x) - sin^4(x...

    2 Answers · Science & Mathematics · 17/05/2010

  10. Does the LHS equal 2tanx / (1+tan^2 x) ? = 2 tan x / sec^2 x = (2 sin x / cos x ) / ( 1/ cos^2 x) = 2 sin x /cos x * cos^2 x = 2 sin x cos x = sin 2x = RHS NB Check your question

    1 Answers · Science & Mathematics · 05/12/2012

  1. Try asking your question on Yahoo Answers